Patients with tuberculous meningitis and hepatitis B co-infection have increased risk for antituberculosis drug-induced liver injury and poor outcomes. Issue 11 (1st November 2020) - Mo, Xichao; Xu, Xuwen; Ren, Zuning; Guan, Junjie; Peng, Jie
Abstract: Background: Tuberculous meningitis (TBM) is one of the most severe forms of tuberculosis. Previous studies reported that hepatitis B virus (HBV) infection could increase the risk of antituberculosis drug-induced liver injury (ATB-DILI) in pulmonary tuberculosis patients. To date, only a few studies exist on the effect of HBV on TBM. Methods: This inpatient study retrospectively analyzed the medical records of patients who were diagnosed with TBM between June 2002 and June 2018. Statistical analysis was used to reveal the difference between the HBV and non-HBV groups. Univariate analysis and multivariate regression analysis were performed on data to determine the prognostic factors of TBM. Results: A total of 386 patients were enrolled in our study, 57 of whom were included in the HBV group and 329 in the non-HBV group. The HBV group showed a higher frequency of ATB-DILI (HBV group: 14.0% versus non-HBV group: 3.3%, p  < .001) and a higher risk of poor outcomes (i.e. death during inpatient period or neurological deficit at discharge, HBV group: 31.6% versus non-HBV group: 19.8%, p  = .045) than the non-HBV group. The multivariate regression analysis identified ATB-DILI, scores of 3–8 on the Glasgow Coma Scale and hydrocephalus as independent predictors of poor outcomes in TBM patients. Conclusions: Our study demonstrated that HBV co-infection could increase the incidence of ATB-DILI and the risk of poor outcomes as identified by three predictors in TBM patients.